War poems : a transgression of objective and linear imagery towards the avant-garde in animation - Conradi, Ina (2021)
From a painter’s perspective, 3D stereo animation provides a fresh method of intensifying and isolating a pictorial space while conveying an illusion of a “real” notion of space and time. The resulting animated painting appears to share its physical space with the viewer. This paper describes the making of “Elysian Fields,” a 3D animated experimental short film that commemorates WWII. It aesthetically and philosophically examines the effect of the representational and abstract qualities of animation and their ability to convey a narrative. This paper will reflect on an art form that has resulted from cross–media exchanges between new media painting and stereoscopic 3D animation. The film’s extremely naturalistic figurative animation visually occupies a contradictory space in relation to the narratives told through surreal and abstract painting. Earlier abstract films by the author influenced the creation of the surreal war film and played a significant role in the structure of the narrative. Furthermore, Elysian Fields was adapted and calibrated for display on various 3D display systems, from large-scale immersive cinematic spaces to an immersive 320˚ theatre at the Nanyang Technological University, Singapore, Ars Electronica’s Deep Space and gallery space installation. Winner of a number of accolades, including multiple “Best Animated 3D Short Film” awards, the film competed with another 56 films for the 86th Academy Awards Qualifying Screening Entry. (http://www.elysianfieldsfilm.com/)